2023
DOI: 10.3390/polym16010042
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Production of Cellulose Nitrates and Bacterial Cellulose from Lignocellulose of Energy Crop

Ekaterina I. Kashcheyeva,
Anna A. Korchagina,
Yulia A. Gismatulina
et al.

Abstract: This study is focused on exploring the feasibility of simultaneously producing the two products, cellulose nitrates (CNs) and bacterial cellulose (BC), from Miscanthus × giganteus. The starting cellulose for them was isolated by successive treatments of the feedstock with HNO3 and NaOH solutions. The cellulose was subjected to enzymatic hydrolysis for 2, 8, and 24 h. The cellulose samples after the hydrolysis were distinct in structure from the starting sample (degree of polymerization (DP) 1770, degree of cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…As the degree of substitution increased, the nitrogen content of the CN samples (Table 2) also increased, while the intensity of hydroxyl peaks became less pronounced. This observation aligns with previous studies reported in [8,11,37,57,58]. Specifically, the CN NA + MC samples exhibited a lower hydroxyl intensity compared to the CN MA samples, consistent with their higher nitrogen content.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As the degree of substitution increased, the nitrogen content of the CN samples (Table 2) also increased, while the intensity of hydroxyl peaks became less pronounced. This observation aligns with previous studies reported in [8,11,37,57,58]. Specifically, the CN NA + MC samples exhibited a lower hydroxyl intensity compared to the CN MA samples, consistent with their higher nitrogen content.…”
Section: Resultssupporting
confidence: 92%
“…OHC was inferior to BC in quality attributes but was characterized by quite high quality values for plant-based cellulose, namely, 93.8% α-cellulose content, 0.8% lignin, 0.8% pentosans, 0.31% ash, and 1450 DP. These high values of quality for OHC are comparable to those of Miscanthus cellulose [11] and higher than those of celluloses from oil palm empty fruit bunch, kenaf fibers [12], coffee pulp [18], giant panda feces, and bitter bamboo stems [19], which were successfully nitrated. The blended cellulose samples had intermediate DP values, comparable to the proportional ratio of BC to OHC.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The representative chemical structure of the CAC comprises O-H (3499 cm −1 ), C-H (2923 cm −1 ), C=O (1759 cm −1 ), and CH 3 (1390 cm −1 ). CB is a suitable conductive material owing to its O-H (3499 cm −1 ) groups, high conductivity, and specific surface area [40][41][42]. In the CACG FT-IR results, the transmittance of C-H and C=O decreased, and the presence of O-H and COO-showed that the CAC was well coated with carbon black.…”
Section: Characterization Of the Conductive Materials Cac And Cacgmentioning
confidence: 99%